ANALISIS VARIASI BAHAN BAKAR PERTAMAX TURBO, AKR, DAN SHELL V- POWER DI KOLABORASI ROTARY R30 TERHADAP PERFORMA MOTOR BENSIN 2-LANGKAH YAMAHA RX-KING 135CC TAHUN 2004 - Putri Sundari; Sugeng Hariyadi; Achmad Rofiqul Jamil (Wahana Teknik, 2022)
The performance of a vehicle is influenced by many things. One of the things that affect is the selection of the type of fuel. In the engine, the mixture of air and gasoline is compressed by the piston to a very small volume and then ignited by the fire generated by the spark plug. Although in society that high octane fuel produces good performance, it is not always the case. The choice of fuel type must be taken into account for the compression ratio of the motor. Like the 2-stroke motor, it is still popular today, because it has great power which is suitable for regions in our country. For a long time, 2-stroke motorcycles have been known as motorbikes that have simple engine construction, large power, exhaust that is not easily porous, and easy to maintain. There is a significant difference between Pertamax turbo fuel, shell-v power, and Akr in terms of performance on a 2004 Yamaha Rx-King 2-stroke motorcycle.